Hambatan Epistemologi Siswa dalam Pembelajaran Geometri Ditinjau dari Gender dan Resiliensi Matematis - Herawati, Annisa Ardana; Anjany, Fadhlillah (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2025)
This study aims to explore students' epistemological obstacles in learning geometry by considering gender factors and mathematical resilience. This research uses the Systematic Literature Review (SLR) method. The literature search process was carried out through systematic stages using four main databases: Google Scholar, SINTA, Scopus, and ERIC (Educational Resources Information Center). The literature search strategy was designed comprehensively by using a combination of specific keywords namely epistemological obstacles, geometry learning, mathematical resilience, gender differences, epistemological obstacles, geometry learning, mathematical resilience, and gender. The articles collected were those whose publication period spanned from 2015 to 2023. From the various articles, 25 articles were selected by researchers that were closely related to the keywords used. The article selection process was carried out through four main stages following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. In this study, it has been identified that students' epistemological barriers in learning geometry are strongly influenced by gender and mathematical resilience factors. Female students tend to show better mathematical communication skills, while male students often face challenges in following the steps of problem solving. In addition, mathematical resilience plays an important role in students' ability to overcome the difficulties they face. Students with high resilience are more able to persevere and try despite challenges, while students with low resilience tend to feel hopeless. Keywords: Epistemological Obstacles, Gender, Mathematical Resilience, Geometry Learning, Systematic Literature Review.